The EU in International Negotiations - Frennhoff Larsén, Magdalena. author. aut Link
XII, 318 p. 1 illus.
Keywords: “Magdalena Frennhoff Larsén’s book makes a welcome and significant contribution to the sparse literature on the EU as an international negotiator. It fills a major gap in our understanding of EU negotiation behaviour by examining the interplay between internal and external bargaining games. The four case- studies brilliantly illustrate the intricacies and complexity of external negotiations. The book will serve as a major reference point for students and scholars alike.” —Ole Elgström, Professor emeritus, Lund University, Sweden “This book is an important and pioneering contribution to our understanding of the EU’s global role. Based on high level interviews with negotiators, it combines a compelling qualitative analysis informed empirically from four case-studies with an insightful application of theories. The analysis is theoretically rigorous and the writing style refreshingly articulate and clear. It is highly recommended and an essential addition to all EU Studies library collections.” —Professor Martin Holland, University of Canterbury, New Zealand “The EU in International Negotiations breaks new ground in providing a comprehensive account of the practices of the EU as an international negotiator. In its cogent analysis drawing comparisons and contrasts between negotiations on trade, development, enlargement and withdrawal negotiations undertaken by the EU it deserves to be widely read by scholars of the EU.” —Professor Richard Whitman, University of Kent, UK This book, which is aimed at scholars, practitioners, advanced under-graduate and post-graduate students, seeks to contribute to the understanding of the EU as an international negotiator by analysing a number of external policy areas where the EU to a great extent engages internationally through negotiations, including development, trade, enlargement, and withdrawal. Magdalena Frennhoff Larsén isSenior Lecturer in the School of Social Sciences, University of Westminster, UK. She teaches EU studies, and her research interests are in the areas of EU external relations. She has published articles on the topic in leading journals, including European Comparative Politics, Journal of Common Market Studies, Journal of European Public Policy, Policy and Politics, and International Negotiation.